2007
DOI: 10.1103/physrevlett.98.096101
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Thickness Evolution of Periodic Twin Domains in Manganite Films Grown onSrTiO3(001)Substrates

Abstract: We present an extended synchrotron x-ray scattering study of the structure of thin manganite films grown on SrTiO3(001) substrates and reveal a new kind of misfit strain relaxation process which exploits twinning to adjust lattice mismatch. We show that this relaxation mechanism emerges in thin films as one-dimensional twinning waves which freeze out into a twin domain pattern as the manganite film continues to grow. A quantitative microscopic model which uses a matrix formalism is able to reproduce all x-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 15 publications
11
37
0
Order By: Relevance
“…The in-plane lattice parameters (a) in Table I [25] and Wei et al [26] and extensively discussed for manganite thin films [27], which are both consistent with the ω scans presented above. These features can also be identified in the 35 nm films.…”
Section: X-ray Diffractionsupporting
confidence: 82%
“…The in-plane lattice parameters (a) in Table I [25] and Wei et al [26] and extensively discussed for manganite thin films [27], which are both consistent with the ω scans presented above. These features can also be identified in the 35 nm films.…”
Section: X-ray Diffractionsupporting
confidence: 82%
“…In addition, we found no evidence of lateral strain modulations, which has been observed in other oxide films and was related to strain accommodation. 23,24 Least-squares fitting was performed where the film structure parameters were allowed to vary while fitting various models to the data, but the bulk STO structure was fixed. The data points near the sharp STO (002) Bragg peak were omitted from fitting because the analysis only considers scattering in the kinematical approximation, and the data in this region do not contain information about the film structure itself.…”
Section: Resultsmentioning
confidence: 99%
“…There might be a relation with the distortion of the LSMO lattice in thin films, as was revealed by high resolution transmission electron microscopy 21,22 and synchrotron XRD. 23 It was found that epitaxial LSMO films, grown by PLD on STO and with a film thickness of less than 100 nm, do not show lattice parameter relaxation but undergo a geometric relaxation toward the rhombohedral distortion of its bulk unit cell without the need for dislocations. Hence, one might expect that this strain relaxation is reflected in the orientation FIG.…”
Section: Discussionmentioning
confidence: 99%